ADSORPSI METHYLENE BLUE OLEH ARANG AKTIF KULIT BUAH LAI (Durio kutejensis (Hassk.)Becc.) - Erfah Sasmita Aulia; Teguh Wirawan; Abdul Aziz (JURNAL ATOMIK, 2025)
Research has been carried out on the adsorption of methylene blue dye with activated charcoal adsorbent prepared from the peel of Lai fruit (Durio Kutejensis (Hassk.) Becc.). This research aims to determine the adsorption characteristics of activated charcoal prepared by the carbonization method at 450°C for 1 hour in a furnace and activated by soaking and shaking in a 2 M HCl activator solution for 24 hours. Characterization of the functional groups of compounds in activated charcoal was carried out using Fourier Transform Infra-Red (FTIR) spectroscopy. The surface morphology of activated charcoal studied by Scanning Electron Microscopy (SEM) shows a large number of pores. The FTIR spectrum of fruit peel activated charcoal reveals the O-H group at wave number 3425.58 cm-1, the C-H group at wave number 2924.09 cm-1, the aromatic C-H group at wave number 1442.75 cm-1, the C-O group at wave number 1319 .31 cm-1. The optimum conditions for adsorption of methylene blue dye were achieved at optimum pH 9, optimum time 60 minutes, optimum temperature 30°C, maximum adsorption capacity 117.965 mg/g by following the Freundlich isotherm and adsorption occurred physically.